Sustainability Report Disclosure and Investor Reaction: An Explanatory Study on Infrastructure Sector Companies - Simbolon, Risna Sari; Odang, Nilam Kemala (JRAM (Jurnal Riset Akuntansi Multiparadigma), 2024)
A good company must be able to control financial and non-financial potential that can increase the company's value and the company's long-term sustainability. Companies can use sustainability reports as a transparent step to increase the company's value which ultimately has an impact on investor confidence. The purpose of this study is to analyze the level of transmission transmission reported by infrastructure sector companies listed on the IDX, and also aims to analyze the impact of transmission publication on investor reactions. This research method uses archival data with a descriptive and explanatory approach. The results and conclusions of this study state that the quality of the cycling cycle is still partially implemented and the impact of the cycling cycle on investors is relatively unresponsive.